Nomogram Model Based on Clinical Risk Factors and Heart Rate Variability for Predicting All-Cause Mortality in Stage 5 CKD Patients - Gao, Xueyan; Wang, Jing; Huang, Hui; Ye, Xiaoxue; Cui, Ying; Ren, Wenkai; Xu, Fangyan; Qian, Hanyang; Gao, Zhanhui; Zeng, Ming; Yang, Guang; Huang, Yaoyu; et al. (Frontiers in Genetics, 2022)
Background: Heart rate variability (HRV), reflecting circadian rhythm of heart rate, is reported to be associated with clinical outcomes in stage 5 chronic kidney disease 5 (CKD5) patients. Whether CKD related factors combined with HRV can improve the predictive ability for their death remains uncertain. Here we evaluated the prognosis value of nomogram model based on HRV and clinical risk factors for all-cause mortality in CKD5 patients. Methods: CKD5 patients were enrolled from multicenter between 2011 and 2019 in China. HRV parameters based on 24-hour Holter and clinical risk factors associated with all-cause mortality were analyzed by multivariate Cox regression. The relationships between HRV and all-cause mortality were displayed by restricted cubic spline graphs. The predictive ability of nomogram model based on clinical risk factors and HRV were evaluated for survival rate. Results: CKD5 patients included survival subgroup (n=155) and all-cause mortality subgroup (n=45), with the median follow-up time of 48 months. Logarithm of standard deviation of all sinus R-R intervals (lnSDNN) (4.4±0.39 vs 4.32±0.42; P=0.007) and logarithm of standard deviation of average NN intervals for each 5 min (lnSDANN) (4.27±0.41 vs 4.17±0.41; P=0.008) were significantly higher in survival subgroup than all-cause mortality subgroup. On the basis of multivariate Cox regression analysis, the lnSDNN (HR=0.35, 95%CI: 0.17-0.73, P=0.01) and lnSDANN (HR=0.36, 95% CI: 0.17-0.77, P=0.01) were associated with all-cause mortality, their relationships were negative linear. Spearman’s correlation analysis showed that lnSDNN and lnSDANN were highly correlated, so we chose lnSDNN, sex, age, BMI, diabetic mellitus(DM), β-receptor blocker, blood glucose, phosphorus and ln intact parathyroid hormone (iPTH) levels to build the nomogram model. The area under the curve (AUC) values based on lnSDNN nomogram model for predicting 3-year and 5-year survival rates were 79.44% and 81.27%, respectively. Conclusion: In CKD5 patients decreased SDNN and SDANN measured by HRV were related with their all-cause mortality, meanwhile, SDNN and SDANN were highly correlated. Nomogram model integrated SDNN and clinical risk factors are promising for evaluating their prognosis.